Preparation of p-sulphonated calix[4]arene functionalised cellulose acetate nanofiber for methylene blue dye removal from aqueous solution - Basri, Nur Amilah Fadlina (2023)
Rapid growth in various industrial sectors, namely, dye related industries, has led to high levels of dye discharged into water resources thus posing threat to the environment and human health. Owing to high effectiveness and low cost, adsorption features as an ideal method for dye removal. Herein, adsorbent material in the form of nanofibers comprised of cellulose acetate based, psulphonated calix[4]arene (p-SOCX) functionalised graphene oxide (GO) were successfully prepared using the electrospinning technique. p-sulphonated calixarene and graphene oxide are promising extractants for benzene-based contaminants such as methylene blue due to the presence of electron-rich benzene rings through π-π interaction. Furthermore, the negatively charged sulfonate groups on the upper rim of p-sulphonated calixarene and oxygen rich functional groups on graphene oxide enable electrostatic and hydrogen bond interactions. Fourier Transform Infrared (FT-IR) spectroscopy and carbonhydrogen- nitrogen-sulphur (CHNS) elemental analysis confirmed the presence of p-sulphonated calixarene within the fiber matrix. Scanning electron microscope (SEM) images of the prepared samples revealed the structural changes upon addition of graphene oxide and p-sulphonated calix[4]arene. The fiber’s surface became rougher upon addition of graphene oxide and increased in fiber diameter was observed with increase in p-sulphonated calix[4]arene. Surface area analysis via Brunauer, Emmet and Teller (BET) method showed that the specific surface area of cellulose acetate/graphene oxide/p-sulphonated calix[4]arene (CA/GO/SOCX) nanofiber was 12.36 m2/g. Thermal profiles of the nanofibers recorded via thermogravimetric analysis displayed slight enhancement in thermal stability after adding graphene oxide to cellulose acetate. However, for samples containing p-sulphonated calix[4]arene, the thermal stability decreased with increase in p-sulphonated calix[4]arene amount. Several reaction parameters namely, pH, adsorbent dosage, dye concentration, contact time, and temperature for methylene blue removal was investigated herein. Results show increased adsorption capacity of methylene blue was achieved in presence of p-sulphonated calix[4]arene compared to pure cellulose acetate nanofiber and cellulose acetate/graphene oxide nanofiber at an ideal pH 8. With an initial MB dye concentration of 10 mg/L, adsorbent dosage of 20 mg/10 mL, and contact time of 60 minutes at room temperature, ca. 298 K, the best removal efficiency was achieved, i.e., 88.84 %. The pseudo-secondorder kinetic was considered to be more accurate to describe the adsorption behavior of MB ions compared to the pseudo-first-order model and intraparticle diffusion model. According to the fitting result of the Langmuir equation, maximum adsorption capacity of CA/GO/SOCX1% reached as high as 175.4 mg/g. The inclusion of p-sulphonated calix[4]arene at appropriate concentrations was observed to lead to a notable enhancement in both the adsorption capacities and the percentage removal of MB ions. The reusability study however shows considerable downfall in adsorption efficiency throughout the fifth cycle which is from 92% to 73%, 59%, 49% and 43% after five times of usage. It can be concluded that CA/GO/SOCX1% has potential to be used as an adsorbent for the methylene blue dye removal from aqueous solution.